Letter to Jane Tolmach; from George Grimes - George Grimes:::::: (1964)
This letter was from George Grimes to Jane Tolmach to send a reminder about the scheduled meeting with Winston O. Wilson on January 18, 1964 at 9:30 am and also that the event will occur on the Friendship Dining Room.